Inhibition of hepatitis B virus subgenotype A1 replication using activators of RNA interference - Mufamadi, Maluta Steven (My University, 2009)
ABSTRACT Infection with the hepatitis B virus (HBV) is still a major global health problem with an estimated 6% of the world’s population chronically infected with the virus. Chronic infection with HBV subgenotype A1, which is hyperendemic to southern Africa, is associated with a particularly high incidence of liver cancer and cirrhosis. Understanding HBV replication and developing effective HBV treatment to prevent liver cancer remain important medical priorities. Although there is a preventative vaccine for HBV, efficacy of currently available treatment of established infection is limited. Exploiting the RNA interference (RNAi) pathway through the use of small interfering (siRNA) and short hairpin RNA (shRNA) is an attractive new approach for the development gene therapies against HBV infection. Our laboratory has designed and demonstrated the efficacy both in vitro and in vivo of several shRNAs designed to target the X open reading frame (ORF) of HBV. Thus, the objective of this study was to construct a replication competent plasmid vector of the A1 subgenotype, a reporter plasmid vector of HBV and to assess the efficacy of RNAi effecters against these vectors both in vitro and in vivo. The first HBV replication competent vector, pCR-HBVA1 1.3x, containing the sequence of an HBV subgenotype A1 isolate, was successfully constructed by generating a greater than genome length sequence of HBV, that starts just upstream of endogenous HBV basic core promoter (BCP) and ends just downstream of the unique HBV polyadenylation (pA) site. Human hepatoma (Huh7) cells transfected with this plasmid secreted HBV surface antigen (HBsAg) into Abstract viii culture supernatants. In the murine hydrodynamic injection model of HBV replication, serum HBsAg, hepatitis B e antigen (HBeAg) and viral particle levels as well as relative surface and core mRNA levels were shown to be significantly elevated as compared to mock-injected mice. The second HBV vector, pCH-FLuc, was successfully generated by replacing the surface ORF with the sequence encoding Firefly Luciferase. The ability of pCH-FLuc to express Firefly Luciferase was demonstrated in a liver cell line (Huh7 cells). Co-transfection of the reporter plasmid, pCH-FLuc, with shRNAs targeted to HBV caused a significant reduction in Luciferase expression. Co-transfection/injection of the pCR-HBVa1 1.3x with shRNAs caused significant inhibition in the level of viral antigens (HBsAg, HBeAg and hepatitis B core antigen (HBcAg) as well as relative surface and core mRNA levels. This was observed both in vitro and in vivo. Our results demonstrate the potential this model allows for the study of HBV replication as well as the assessment of potential therapeutic strategies in a regionally significant subgenotype of HBV.
Keywords: hepatitis B virus; subgenotype A1